PENGEMBANGAII MODEL PEMBELAJARAN BERBASIS DEEP DIALOGUE/CRITICAL THINKING MELALUI PRAKTIK BELAJAR KEWARGANEGARAAN SISWA SD DI JAWA TIMUR - Sri Untari; Suparlan Al Hakim; Ketut Diara Astawa (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2010)
Abstract: This study developed a leaming-based model of deep dialogue / crticai thinking in the practice of citizenship 1eaming. The research was conducted in East Java SD in three stages by using the design ofresearch and development. Data were collected through questionnaires, observations and interviews and analyzed descriptive statistical analysis techniques. The results found (l) carrying capacity sufficient to support schools (2) the anangement is conducive school atmosphere (3) implementation of the elementary civics lesson in East Java is relatively conventional, less can enhance the activity, creativity and a sense of happy students. Based learning model prototype DD / CT with sintax: silence, Concept Attainment, build community, cooperatif learning, and silence has many theoretical advantages.